2015
DOI: 10.1016/j.cub.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The Speed of Alpha-Band Oscillations Predicts the Temporal Resolution of Visual Perception

Abstract: Summary Evidence suggests that scalp-recorded occipital alpha-band (8-13 Hz) oscillations reflect phasic information transfer in thalamocortical neurons projecting from LGN to visual cortex [1–5]. In animals, the phase of ongoing alpha oscillations has been show to modulate stimulus discrimination and neuronal spiking [6]. Human research has shown that alpha phase predicts visual perception of near-threshold stimuli [7–11] and subsequent neural activity [12–14], and that the frequency of these oscillations pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

61
473
10
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(548 citation statements)
references
References 25 publications
61
473
10
4
Order By: Relevance
“…Similarly, Matthewson et al (2009) demonstrated that posterior alpha phase predicts awareness for a metacontrast masking paradigm. Consistent with this, Samaha and Postle (2015) showed that resting and ongoing occipital alpha frequency predicts perception for one-versus two-flash discrimination. If individuals' occipital PAF at rest determines the frequency with which their representations are updated, then we would expect to see a relationship between phase at offset and performance.…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, Matthewson et al (2009) demonstrated that posterior alpha phase predicts awareness for a metacontrast masking paradigm. Consistent with this, Samaha and Postle (2015) showed that resting and ongoing occipital alpha frequency predicts perception for one-versus two-flash discrimination. If individuals' occipital PAF at rest determines the frequency with which their representations are updated, then we would expect to see a relationship between phase at offset and performance.…”
Section: Discussionsupporting
confidence: 59%
“…Brain oscillations have been already proposed as a mechanism to instantiate temporal predictions when sensory information has a regular structure484950 and to explain some illusions in the temporal domain5152. Interestingly, the idea that brain rhythmic activity could serve to parse sensory information and order events in time has been already explored a few decades ago5354 and corroborated by most recent studies showing that the power55, the phase5657 as well as the frequency58 of brain oscillations affect simultaneity judgments and sensory fusion-thresholds.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have suggested that the peak frequency (i.e., the frequency with the maximal power) of alpha-band (8–12 Hz) oscillations in parieto-occipital areas serves as the neuronal correlate of such perceptual cycles in the (audio-) visual domain (Cecere et al, 2015; Samaha and Postle, 2015). Here, we studied in a tactile temporal discrimination task whether peak frequencies might likewise serve as a correlate for perceptual cycles in the somatosensory domain.…”
Section: Discussionmentioning
confidence: 99%